Blockchain Technology for Supply Chain Management - TUNABOYLU, BAHADIR (My University, 2022)
Blockchain technology offers important opportunities for the supply chain management. This paper aims to overview the employment of blockchain technology in the field of the supply chain. Although the technology has been widely associated with cryptocurrencies, non-financial applications such as supply chain, power, and food industry are also promising. Blockchain can provide a permanent, shareable, auditable record of products through their supply chain, which improves product traceability, authenticity, and legality in a more cost-effective way. In this chapter, the potential improvement expectations via blockchain technology for the case of agribusiness were discussed. The proposed case for automotive manufacturing-micro factory with blockchain technology was also introduced.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; Endüstri Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; Industrial Engineering; Engineering and Technology; MÜHENDİSLİK, ENDÜSTRİYEL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); YÖNETİM; Ekonomi ve İş; Sosyal Bilimler (SOC); ENGINEERING, INDUSTRIAL; ENGINEERING; Engineering, Computing & Technology (ENG); MANAGEMENT; ECONOMICS & BUSINESS; Social Sciences (SOC); General Decision Sciences; Decision Sciences (miscellaneous); General Engineering; Engineering (miscellaneous); Social Sciences & Humanities; Physical Sciences; Supply chain; Blockchain; Survey; Smart contract